Meaning of The Symbol of The Mulutna Figure in Sukuraga Puppet - Aulia, Regina Putri (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2023)
The content of the discussion is about puppet, symbol, and the meaning in one of the figure in the puppet. Puppet is one of the traditional 2-dimensional entertainment media, which can be seen and also felt. A puppet always contains a message in it related to the conditions of life in the world that we live. In West Java, especially in Sukabumi, there is a Sukuraga puppet created by an extraordinary artist named Effendi. Mr. Effendi created Sukuraga puppet, where this Sukuraga means "limbs" because the shapes of the puppets are a reflection of the shape of the human body. It aims to remind people that there will be consequences for all actions. There are 9 Sukuraga puppet characters, one of which is the mouth, each character has symbols and meanings that we can learn from and relate them to various phenomena that exist in the world we currently live in. The method used is descriptive qualitative because the research was conducted by conducting direct interviews with informants to obtain more detailed information.